2018
DOI: 10.1111/asj.13140
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a high energy and low protein diet on hepatic and plasma characteristics and Cidea and Cidec mRNA expression in liver and adipose tissue of laying hens with fatty liver hemorrhagic syndrome

Abstract: Cidea and Cidec are two members of Cell death-inducing DNA fragmentation factoralpha-like effector family proteins, which could be involved in lipid or fat metabolism.To better understand the roles of Cidea and Cidec in fatty liver hemorrhagic syndrome (FLHS), 150 healthy 155-day-old Hyline Brown laying hens were randomly divided into control group (fed with basic diet) and experimental group (fed with high-energy low-protein [HELP] diet). Analysis of the liver by tissue sectioning and hematoxylin and eosin st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…PLIN1 was found to interact with CIDEC to promote LD formation by activating the PPARG signaling pathway [4042]. According to published reports, higher PLIN1 and CIDEC expression promoted higher fat accumulation in chickens [43]. In this study, CIDEC and PLIN1 were all upregulated in the HTG group, which is consistent with their increased TG content.…”
Section: Discussionsupporting
confidence: 83%
“…PLIN1 was found to interact with CIDEC to promote LD formation by activating the PPARG signaling pathway [4042]. According to published reports, higher PLIN1 and CIDEC expression promoted higher fat accumulation in chickens [43]. In this study, CIDEC and PLIN1 were all upregulated in the HTG group, which is consistent with their increased TG content.…”
Section: Discussionsupporting
confidence: 83%
“…Hens fed a HF diet [4][5][6][7] or HFLP diet [1,[9][10][11][12] have been created for studying the pathogenesis of FLHS in laying hens or as a model for human NAFLD investigation. The pathological characters of FLHS include hepatic fat accumulation in the liver with hemorrhage or rupture.…”
Section: Discussionmentioning
confidence: 99%
“…It is associated with approximately 40% of the necropsied hens, and can be up to 74% in the caged laying hens [2]. Several factors have been relate to FLSH, such as nutritional, metabolic, hormonal, environmental, and genetic factors [1,2], but excess energy intake is the fundamental player as FLHS can be induced by a high-fat diet (HFD) [4][5][6][7][8] or a high fat and low protein (HFLP) diet [1,[9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Cidea and Cidec are effector factors inducing cell death. Peng et al (2019) showed that FLHS significantly increased the expression levels of Cidea and Cidec mRNA in liver and adipose tissue, and both could be lipid droplet-associated proteins that play an important role in promoting hepatic lipid accumulation and steatosis. In addition, high expression of Cidea and Cidec promoted lipid accumulation in mouse liver, but silencing Cidea and Cidec reduced hepatic lipids.…”
Section: Molecular Mechanismsmentioning
confidence: 98%
“…Vegetable oil contains a lot of unsaturated fatty acids (PUFA), and PUFA has the effect of regulating lipid metabolism. Studies have shown that n-3 PUFA can significantly reduce liver fat (Peng et al 2019). In addition, adding sunflower oil and linseed oil to the diet can significantly reduce the fat content of the liver of laying hens and inhibit the occurrence of FLHS.…”
Section: Addition Of Vegetable Oilmentioning
confidence: 99%